The Impact of the Moratorium Policy on Fishery Companies (PT) in Sorong City - Arifin; Roger R. Tabalessy; Tessa Rakian (Lembaga Penelitian dan Pengabdian, Universitas Kristen Papua, 2024)
This study aims to determine the impact of the moratorium on the operation of (PT) fishery in Sorong and for export activities of fisheries, especially commodities demersal fish and shrimp. The moratorium imposed on large ships over 30 GT, ship construction abroad, boats that use trawling gear and replace the court transhipment at sea. This research conducted in the area of Sorong by selecting the relevant agencies are performed in the unit supervisor PSDKP Sorong, Syahbandar fisheries, and fishing companies to conduct interviews and collect data relating to the object of research that matters concerning the company's operations and activities of fishery product exports. Of the results of research conducted, the impact of the moratorium on the operation of (PT) fishery is the discontinuation of the company's operations in Sorong area, the export of fishery products stalled, stalled enlargement levy export fishery products to the local government, the termination of employment of the crew, activities loading and unloading in the fishing port decreases. The impact of the moratorium is not profitable for the company (PT) fishery, income levies, the livelihood of the crew and the fishing port of Sorong city workers.